EXPERIMENTAL STUDY OF MINERAL SURFACE AND AQUEOUS ALUMINUM COMPLEXATION WITH ANILINE AND 2-CHLOROANILINE - APPLICATION OF A SURFACE COMPLEXATION MODEL - Yane L.; Fein J.B. (My University, 1998)
The thermodynamic stabilities of the aqueous and surface Al-aniline and Al-2-chloroaniline complexes were investigated using solubility and adsorption experiments. Aqueous complexation was studied by measuring the solubility of gibbsite (Al(OH)3) as a function of aniline and chloroaniline concentrations. Experiments measuring aniline and chloroaniline adsorption onto corundum (α-Al2O3) were conducted as a function of pH, from pH 1.5 to 9.0, at room temperature in 0.1 molal NaCl solutions, with starting concentrations of 10-3.0 and 10-3.3molal aniline, 10-2.7 molal 2-chloroaniline, and 2.72 x 10-3 molal total surface sites.The experiments place quantitative constraints on the thermodynamic properties of the aqueous and the surface Al-aniline complexes. The solubility data indicate that if Al-aniline or Al-2-chloroaniline aqueous complexes exist, they are not stable enough to significantly affect the solubility of gibbsite under the experimental conditions. Conversely, the adsorption data provide unequivocal evidence for the presence of two distinct surface Al-aniline and Al-chloroaniline complexes according to the following reactions(1) Aniline0 + =Al(OH)0 # =AlOH(Aniline)0(2) Aniline0 + =Al(O)- # =AlO(Aniline)-(3) Chloroaniline0 + =Al(OH)0 # =AlOH(Chloroaniline)0(4) Chloroaniline0 + =Al(OH2)+ # =AlOH2(Chloroaniline)+We use a constant capacitance model to quantify the stability constants for reactions 1-4, and the results yield log equilibrium constant values of 2.09, 2.67, 2.87, and 2.30, respectively. The experimental results indicate that for most contaminated systems, aqueous Al-aniline, and Al-chloroaniline complexation does not have a significant effect on aniline speciation in groundwater, but that mineral surface complexation can significantly affect total aniline and chloroaniline budgets.